Prosedur Penarikan Produk dan Pengelolaan Produk Kembalian dalam Rantai Distribusi Farmasi - Niken Widya Ningrum; Nur Latipah Sulistiawanti; Nor Latifah (An-Najat, 2025)
Product recall and returned product management are essential in ensuring the quality, safety, and efficacy of pharmaceutical preparations in circulation. Data were obtained from various journals and official reports from 2018 to 2024 relevant to pharmaceutical recalls. With effective recall mechanisms, customer safety and quality of pharmaceutical services are anticipated to enhance continuously. This review highlights the significance of strengthening effective recall systems, human resource training, and the use of digital technology in distribution processes. This article aims to thoroughly examine the procedures for product recall and returned product management within the pharmaceutical distribution chain through a literature study. The review shows that despite the availability of national and international regulations, implementation still faces difficulties such as absence of unified information systems, insufficient collaboration among industry players and authorities, and less than optimal quality culture in the field. Additionally, difficulties in product tracking, documentation, and recall decision-making are also concerns.